2020
DOI: 10.4236/ojas.2020.103024
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Raw Camel Milk by Lactoperoxidase System Using Hydrogen Peroxide Producing Lactic Acid Bacteria

Abstract: This study was conducted to investigate the effect of lactic acid bacteria (LAB) activated lactoperoxidase system (LPs) on keeping quality of raw camel milk at room temperature. Camel milk samples were collected from Errer valley, Babile district of eastern Ethiopia. The level of hydrogen peroxide (H 2 O 2 ) for activation of LPs was optimized using different levels of exogenous H 2 O 2 . Strains of LAB (Lactococcus lactis 22333, Weissella confusa 22308, W. confusa 22282, W. confusa 22296, S. Infatarius 22279 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to publications [79]- [81], for effective milk antibacterial treatment, a minimal H 2 O 2 concentration of 0.01 %, which is equivalent to 2.9 mM, is used. This value significantly exceeds the calculated LOD for our sensor.…”
Section: Resultsmentioning
confidence: 99%
“…According to publications [79]- [81], for effective milk antibacterial treatment, a minimal H 2 O 2 concentration of 0.01 %, which is equivalent to 2.9 mM, is used. This value significantly exceeds the calculated LOD for our sensor.…”
Section: Resultsmentioning
confidence: 99%
“…The only change obtained in Majahem that at age >7 years showed that serum IgG was significantly higher than their corresponding groups at age<7 years that reflect the tendency of SCM characteristic of increased SCC and bacteriological examination. IgG is a part of the immune system that has several biological functions, including antibacterial and anti-inflammatory qualities (Dashe et al 2020). According to Thorsteinsdottir et al (2019), acute inflammation may cause the mammary gland's blood-to-milk permeability barriers to be destroyed, which increases the passive transfer of IgG into milk and causes an increase in IgG output.…”
Section: Discussionmentioning
confidence: 99%
“…(Yassin et al 2015;El-Fakharany et al 2017). Activation of LPS has been investigated as a potential alternative technique for maintaining milk safety by eliminating pathogenic microbes (Dashe et al 2020;Mohamed and El Zubeir 2020).…”
Section: Introductionmentioning
confidence: 99%